Answer:
4. ¹₁H + ¹³₆C —> ¹⁴₇N + γ
5. ¹₀n + ¹⁰₅B —> ⁷₃Li + ⁴₂He
6. ⁴₂He + ¹⁴₇N —> ¹⁷₈O + ¹₁H
Step-by-step explanation:
4. ¹₁H + ¹³₆C —> ¹⁴₇N + __
Let ᵇₐX be the unknown.
Thus, the equation becomes:
¹₁H + ¹³₆C —> ¹⁴₇N + ᵇₐX
Next, we shall determine b, a and X. This is illustrated below:
For b:
1 + 13 = 14 + b
14 = 14 + b
Collect like terms
b = 14 – 14
b = 0
For a:
1 + 6 = 7 + a
7 = 7 + a
Collect like terms
a = 7 – 7
a = 0
Therefore,
ᵇₐX => ⁰₀X => γ
Thus, the balanced equation is
¹₁H + ¹³₆C —> ¹⁴₇N + γ
5. ¹₀n + ¹⁰₅B —> __ + ⁴₂He
Let ˣᵧA be the unknown.
Thus, the equation becomes:
¹₀n + ¹⁰₅B —> ˣᵧA + ⁴₂He
Next, we shall determine x, y and A. This can be obtained as follow:
For x:
1 + 10 = x + 4
11 = x + 4
Collect like terms
x = 11 – 4
x = 7
For y:
0 + 5 = y + 2
5 = y + 2
Collect like terms
y = 5 – 2
y = 3
Therefore,
ˣᵧA =>⁷₃A => ⁷₃Li
Thus, the balanced equation is:
¹₀n + ¹⁰₅B —> ⁷₃Li + ⁴₂He
6. ⁴₂He + ¹⁴₇N —> __ + ¹₁H
Let ᶜₑG be the unknown.
Thus, the equation becomes:
⁴₂He + ¹⁴₇N —> ᶜₑG + ¹₁H
Next, we shall determine c, e and G. This can be obtained as follow:
For c:
4 + 14 = c + 1
18 = c + 1
Collect like terms
c = 18 – 1
c = 17
For e:
2 + 7 = e + 1
9 = e + 1
Collect like terms
e = 9 – 1
e = 8
Therefore,
ᶜₑG => ¹⁷₈G => ¹⁷₈O
Thus, the balanced equation is:
⁴₂He + ¹⁴₇N —> ¹⁷₈O + ¹₁H